Pola Komunikasi Kelompok Best Young Leader dalam Mempertahankan Eksistensi Falp di IPB University - Tania Nurrahmawati; Suparman Suparman; Amiruddin Saleh; Rici Tri Harpin Pranata; Nabhila Manisya; Khalila Zahra Maharani; Maharani Azzahra (CV. ULIL ALBAB CORP, 2025)
The Future Agile Leader Program (FALP) at IPB University aims to cultivate leadership skills among students and young leaders through adaptive group communication patterns. This study seeks to analyze the communication strategies employed by the Best Young Leaders in maintaining the program's existence and to explore the dynamics between organizers and participants in ensuring its sustainability. Utilizing a qualitative methodology, in-depth interviews were conducted with GYP (20 years old), one of FALP's distinguished young leaders. The findings reveal that adaptive communication patterns, grounded in responsiveness to the challenges of the digital era, leverage a hybrid approach of online and offline interactions (O2). Central to this framework are two-way communication and transparency, which foster collaboration and synergy among group members. Robust internal communication enhances each member's regarding their roles, significantly contributing to the group's success. Moreover, harmonious relationships between organizers and participants emerge as a pivotal factor in sustaining the program. This study concludes that adaptive and collaborative communication frameworks serve as a foundational pillar in ensuring FALP's longevity. Future recommendations include further exploration of the interplay between technology and self-awareness in elevating communication quality within leadership development initiatives.